The Effects of Sports Drinks During High-Intensity Exercise on the Carbohydrate Oxidation Rate Among Athletes: A Systematic Review and Meta-Analysis - Li, Xudong; Wang, Wanxia; Guo, Rui; Wang, Anqi; Wei, Chaojun (Frontiers in Physiology, 2020)
Background: This study examines the effects of sports drinks ingestion during high-intensity exercise for carbohydrate oxidation rate (CHO-O) among athletes. Methods: PubMed, Embase, and the Cochrane library were searched for available papers published up to November 2019. The primary outcome is the carbohydrate oxidation rate (CHO-O), and the secondary outcome is the fat oxidation rate (Fat-O). Statistical heterogeneity among the included studies was evaluated using Cochran’s Q-test and the I2 index. The random-effects model was used for all analyses, regardless of the I2 index. Results: Five studies are included, with a total of 58 participants (range, 8-14/study). All five studies are randomized cross-over trials. Compared to the control beverages, sports drinks have no impact on the CHO-O of athletes (WMD=0.29, 95%CI: -0.06-0.65, P=0.106; I2=97.4%, P<0.001) and on the Fat-O of athletes (WMD=-0.074, 95%CI: -0.19-0.06, P=0.297; I2=97.5%, P<0.001). Carbohydrate-electrolyte solutions increase CHO-O (WMD=0.47, 95%CI: 0.08-0.87, P=0.020; I2=97.8%, P<0.001), but not Fat-O (WMD=-0.14, 95%CI: -0.31-0.03, P=0.103; I2=98.2%, P<0.001). Caffeine has a borderline effect on Fat-O (WMD=0.05, 95%CI: 0.00-0.10, P=0.050). Conclusions: Compared with the control beverages, sports drinks show no significant improvement in CHO-O and FAT-O in athletes. Carbohydrate-electrolyte solutions increase CHO-O in athletes, but not Fat-O.